1996
DOI: 10.3354/meps131307
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of DMSP-lyase in Phaeocystis sp. (Prymnesiophyceae)

Abstract: The marine phytoplankton species Phaeocystis sp. is one of the few microalgae known to be able to convert dimethylsulfoniopropionate (DMSP) enzymatically into dimethyl sulfide (DMS) and acrylic acid. The function of this enzymatic process for the organism is not known. From experiments with crude extracts and whole cells of axenic cultures of Phaeocystis it was concluded that DMSP-lyase is membrane-bound and located extracellularly because: (1) the enzyme activity in extracts and in whole cells varied in a sim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
79
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(83 citation statements)
references
References 16 publications
(15 reference statements)
3
79
1
Order By: Relevance
“…This is particularly relevant for organisms with a thick boundary layer such as Phaeocystis colonies. The idea of such a role for DMSP-lyase was instigated by the observations that Phaeocystis exhibits high in vivo lyase activities when dissolved DMSP is added to the culture medium and that extracellular inhibitors can repress this activity (Stefels and Dijkhuizen 1996). In addition, it has been observed that acrylate, one of the products of DMSP degradation, accumulates in the mucus layer of Phaeocystis colonies (Noordkamp et al 2000), which is in agreement with an extracellular location of the enzyme.…”
Section: Maintenance Of Intracellular Dmsp Concentration: Algal Dmsp-mentioning
confidence: 69%
“…This is particularly relevant for organisms with a thick boundary layer such as Phaeocystis colonies. The idea of such a role for DMSP-lyase was instigated by the observations that Phaeocystis exhibits high in vivo lyase activities when dissolved DMSP is added to the culture medium and that extracellular inhibitors can repress this activity (Stefels and Dijkhuizen 1996). In addition, it has been observed that acrylate, one of the products of DMSP degradation, accumulates in the mucus layer of Phaeocystis colonies (Noordkamp et al 2000), which is in agreement with an extracellular location of the enzyme.…”
Section: Maintenance Of Intracellular Dmsp Concentration: Algal Dmsp-mentioning
confidence: 69%
“…The cleavage of DMSP to DMS and acrylate is accomplished enzymatically via DMSP-lyase which has been shown to exist in marine bacteria , de Souza & Yoch 1995a, Yoch et al 1997. There are also a few species of phytoplankton which are known to possess DMSPlyase (Stefels & Dijkhuizen 1996, Steinke et al 1998, and it is speculated that there may be others. The relative contribution of phytoplankton to marine DMS production is presently unknown, but may be significant in regions where DMSP-lyase-containing algal species are abundant.…”
Section: Introductionmentioning
confidence: 99%
“…Once in solution, DMSP can be utilized by many bacteria as a sulfur, carbon or energy source via catabolic demethylation to 3-methylmercaptopropionate and 3-mercaptopropionate (Kiene and Linn, 2000;Howard et al, 2006). Bacteria have also been shown to enzymatically cleave DMSP to DMS and acrylate (Kiene, 1993;Ledyard and Dacey, 1996;Stefels and Dijkhuizen, 1996;Steinke and Kirst, 1996) and novel evidence suggests DMSP-dependent DMS-production without the release of acrylate (Todd et al, 2007). DMS can be used as a metabolite by bacteria (Vila-Costa et al, 2006), photochemically degraded at the sea surface (Brimblecombe and Shooter, 1986;Kieber et al, 1996), or transferred to the atmosphere (Liss and Slater, 1974).…”
Section: Introductionmentioning
confidence: 99%